Penerapan Triple Bottom Line Pada PT Bank Rakyat Indonesia Tbk - Fara Brygita Ramadhani; Cholis Hidayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research analyzes the implementation of the Triple Bottom Line (TBL) concept by PT Bank Rakyat Indonesia (BRI) in their 2022 sustainability report, using a qualitative descriptive analysis method. The TBL concept, encompassing